Hubungan Ideal antara Partai Politik Nasional dengan Partai Politik Lokal dalam Pengisian Jabatan Publik - Armia, Muhammad Siddiq (Jurnal Review Politik, 2017)
There are questions regarding the mechanism of fulfilling public position in democratic countries. The main question is how local party and national party can deal with prominent position, is it pointed or elected by party mechanism? This article will explore this main problem, including to fulfil public positions. To answer those questions, writer uses comparative political approach, using Germany as comparative country. In Indonesian, not all public positions regulated by regulations, chiefly in provincials’ level.